A&T Ethiopia Adolescent Nutrition Baseline Survey 2019: Adolescent Girl - International Food Policy Research Institute (International Food Policy Research Institute, 2022)
Alive & Thrive (A&T) is an initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition, breastfeeding and complementary feeding practices. In Ethiopia, A&T implemented a package of adolescent nutrition interventions through school-based (flag assemblies, classroom lessons, girls’ clubs, peer mentoring, weight and height measurement, and parent-teacher meetings) and community platforms (health post and home visits and community gatherings). This dataset is part of a survey that was conducted to gather baseline data for the impact evaluation of the interventions. The overall study objective was to determine the feasibility of delivering nutrition interventions primarily through school-based platforms and their impact on diet quality among adolescent girls. Research questions include: 1) What is the program impact on the diet of adolescent girls: (1) dietary diversity, (2) meal frequency, and (3) less consumption of unhealthy snacks? 2) What is the exposure to adolescent nutrition interventions delivered through school-based platforms? 3) What factors influenced the integration of adolescent nutrition interventions into school-based platforms and their outcomes? The evaluation used a two-arm cluster-randomized, non-masked trial design, consisting of two cross-sectional surveys of in-school adolescent girls aged 10-14 years enrolled in grades 4-8. The unit of randomization is the primary school which includes grades 1-8. The baseline survey was conducted in October-November 2019 by Addis Continental Institute of Public Health (ACIPH), the in-country research collaborator for the survey. The baseline survey included the following: 1) Adolescent girl questionnaire, 2) Parents questionnaire, 3) Teacher/Principal questionnaire, 4) Health Extension Worker (HEW) questionnaire, and 5) Primary school observation checklist. The adolescent girl interviews were conducted using pretested, structured questionnaires. Information was collected on adolescent background, school attendance, meal and snacking patterns, home food environment, nutrition knowledge, WASH practices, health and health-seeking behavior, social desirability, parental interaction, and other influencers (including sharing education messages and materials), gender and marriage beliefs, decision-making power, and anthropometry.